1978
DOI: 10.1104/pp.62.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Assimilation and Translocation in Soybean Leaves at Different Stages of Development

Abstract: Carbon assimilation, translocation, and associated biochemical characteristics of the second trifoiolate leaf (numbered acropetally) of chambergrown soybean, Glycine max (L.) Meff., plants were studied at selected stages of leaf development during the period from 10 to 25 days postemergence. Leaves of uniform age were selected on the basis of leaf plastochron index (LPI).The test leaf reached ful expansion (A..) and maximum CO2 exchange rates on a leaf area basis at 17 days postemergence (LPI 4.1). Maximum ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
1
3

Year Published

1980
1980
1989
1989

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 22 publications
4
72
1
3
Order By: Relevance
“…Spinach leaf SPS is activated by glucose-6-P and inhibited by Pi (6). In studies with spinach leaf protoplasts, Stitt et al (25) reported that cytosolic [glucose-6-P] decreased as CER was reduced. It is likely that cytosolic [Pi] increased as the concentration of P-esters such as glucose-6-P decreased.…”
Section: C02 Enrichment and Water Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinach leaf SPS is activated by glucose-6-P and inhibited by Pi (6). In studies with spinach leaf protoplasts, Stitt et al (25) reported that cytosolic [glucose-6-P] decreased as CER was reduced. It is likely that cytosolic [Pi] increased as the concentration of P-esters such as glucose-6-P decreased.…”
Section: C02 Enrichment and Water Stressmentioning
confidence: 99%
“…Thus, metabolic regulation of SPS may coordinate the rate of sucrose formation in the cytosol with the rate of C-assimilation in the chloroplast when CERs are low. However, when CER is high (light-saturated), sucrose formation may be limited by the maximum activity of SPS (12,13,24,25). Consequently, short-term CO2 enrichment of soybean plants did not result in increased rates of export even though CER was increased (14).…”
Section: Introductionmentioning
confidence: 99%
“…SPS is subject to metabolic regulation (1,7,10), and furthermore, its maximum activity, as measured in leaf extracts, appears to reflect the capacity of the sucrose biosynthetic path- ' way. For example, the activity of SPS increases during leaf expansion concurrent with increased rates of sucrose formation and export (9,16,21). In fully expanded leaves, SPS activity varies among different genotypes and in general, higher activities of SPS in leaf extracts have been associated with increased partitioning of carbon into sucrose and decreased formation of starch (11-13, 20, 21).…”
mentioning
confidence: 99%
“…Translocation in K-deficient leaves may be restricted by reduction in the rate of synthetic metabolism in general (5) or sucrose formation in particular (27); entry ofsucrose into the transport pool (1); or inhibition ofsome step involved in phloem loading (16,30). In unstressed soybean leaves, several studies have suggested that the rate of assimilate export may be related to the activity of SPS (7,10,11 25,26). However, studies have not been conducted with soybean plants to determine the relative impact of K-nutrition on export rate with respect to CER, or SPS activity.…”
mentioning
confidence: 99%